Influence of Price and Timeliness of Delivery Towards Customer Satisfaction (Shopee Express, Hub Koja, Plumpang, Semper, North Jakarta) - Nurkhoiriyah, Syiffa; Hidayat, Yusup Rachmat (Institut Ilmu Sosial dan Manajemen STIAMI, 2024)
The existence of customer dissatisfaction on the price and timeliness of delivery of goods carried out by Shopee Express Hub Koja, and in the last 3 months experienced price instability and timeliness in delivery of goods. This study aims to determine how much influence the price and timeliness of delivery to customer satisfaction on Shopee Express, Hub Koja, Plumpang, Semper, North Jakarta. The independent variables in this study are the price (X1) and timeliness of delivery (X2), and the dependent variable is customer satisfaction (Y). This study uses quantitative methods with a population that is not known to ensure the number of customers. The sample size was 108 respondents. Sampling is done by Accidental Sampling method. Data analysis techniques used in this study are research instrument test and hypothesis test. The results showed that based on the correlation test variable price and delivery timeliness together have a very strong relationship of 0.810 or 81%. And known by the test coefficient of determination of 65.6% while the remaining 34.4% is influenced by other variables not studied in this study. In addition, based on the results of the simultaneous Test (Test F) has a value Fcount > Ftable is equal to (99.903 > 3.08) which means that the price and timeliness of delivery simultaneously positive effect on customer satisfaction variables. H0 is rejected and H3 is accepted